The Representation of the Inner Speech on «El reino de Celama» by Luis Mateo Díez: a Choral Polyphony: a choral polyphony (Castilla. Estudios de Literatura, 2017)
The aim of this article is to analyze the inner speech on El reino de Celama by Luis Mateo Díez, a literary cycle composed by El espíritu del páramo (1996), La ruina del cielo (1999) y El oscurecer (un encuentro) (2002). To this purpose, it deems appropriate to delve into the evolution of the inner voices (Ismael Cuende's doctor and Rapano's shepherd) that integrate the coral polyphony as the main source of the novel. Throughout this pages, the study expects to fill a gap in this discursive approach that the specialised critic has not dedicated a thorough reflection.
Keywords: Celama's cycle; Luis Mateo Díez; inner speech; polyphony; choral novel